Strategi Manajemen Distribusi Islam Dalam Mengatasi Krisis Ekonomi Akibat Pandemi Covid-19 - Nurul Fadhilah (Entrepreneurship Faculty, Universitas Garut, 2020)
Abstract - Besides having an impact on health, Covid-19 also has an impact on the Indonesian economy. This happened because restrictions on human movement directly resulted in the impact of the economic crisis. Islamic economic theory can be used as a strategy in recovering the economic crisis. This study aims to formulate Islamic economic theories and models in overcoming economic crises.. This research method is desctiptive with literature study analysis. The results of this study are that the islamic distribution system has the principle of equitable distribution of wealth. The islamic distribution system is divided into two, namely a commercial distribution system and a distribution system that is based on social aspect. Commercial distribution can be in the form of a cooperation contract with a non-usury contract, while the distribution in the social aspect is in the form of zakat, infaq, shadaqah, waqf, and inheritance.